سردية النص الرحلي بين التاريخية والأدبية "رحلة ابن جبير " -أنموذجا- - سيلت, أم الخير; دغمان, علي (جامعة الوادي - University of Eloued, 2023)
فن الرحلة لون أدبي ذو طابع قصصي يحوي الفائدة للمؤرخ والأديب و غيرهما ،فإذا بحثت عن التاريخية تجدها ظاهرة للعيان ،فالرحلة و إن كانت من البداية مؤرخة بكل ماتحويه الكلمة من معنى في ذكرها للحوادث ،أو دقّة وصف للأشخاص والأماكن وغيرها بأسلوب متنوع ،وهذا راجع لمكنة الرّحالة وانطباعه الشّخصي ،إلا أنّه قد يصل بإبداعه حد الأدبية الّتي تجعله ينفرد بسرده الذي ينطلق فيه من الواقع وقد يشبعه بالخيالية والعجائبية بل حتى أنه قد يجمع فيه أجناسا أدبية وغير أدبية من حكايات ومرويات وخرائط ورسوم وصيغ مقالية ومحطات سردية وأصوات متعددة ...الخ. تجعله ينقل رحلته من مجرد رحلة سفر عادية الى جمالية فنية عن طريق خطاب جامع ماتع يكمل متعة ودهشة سفره لينافس بهذه القطعة الفنية مصاف آداب عالمية متنوعة Travel literature is a literary genre that owns a story-telling feature and contains a moral for the historian, writer and others. If you searched about historicism, you can find visible to the reader though it was initially historical in reporting events literally or precision in the depiction of characters, places and others with a varied style relatively to both the status of the traveler and his personal impression. Despite this, he can reach literary that makes him lead with his narration initially from his actuality. He may enrich it with fiction and wonder and he even may gather literary and non-literary genres from stories, narratives, maps, cartoons, article-based forms, narratives, and multiple voices etc. These make him depict his travel from a plain one into an artistic aesthetic by means of collective and enjoyable discourse that completes enjoyment and wonder of his travel with this masterpiece various world literary works.
Keywords: الرحلة، السردية ،تاريخية، النص الرحلي، أدبية النص الرحلي; travel, narrative, historical, text, travel text, travel-text literary